Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/17441692.2016.1153122
|View full text |Cite
|
Sign up to set email alerts
|

‘People like me don't make things like that’: Participatory video as a method for reducing leprosy-related stigma

Abstract: The Stigma Assessment and Reduction of Impact project aims to assess the effectiveness of stigma-reduction interventions in the field of leprosy. Participatory video seemed to be a promising approach to reducing stigma among stigmatized individuals (in this study the video makers) and the stigmatisers (video audience). This study focuses on the video makers and seeks to assess the impact on them of making a participatory video and to increase understanding of how to deal with foreseeable difficulties. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…Studies were published between 1998 and 2018, 14 were conducted in low‐ and middle‐income countries and 5 in developed countries. The most represented countries were Indonesia, India and the United Kingdom . Study designs varied considerably: 3 (cluster‐)randomized controlled trials, 2 quasi‐experimental studies, 3 case‐control studies and 3 cohort studies were supplemented by 5 qualitative studies, 2 case studies and a secondary data analysis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were published between 1998 and 2018, 14 were conducted in low‐ and middle‐income countries and 5 in developed countries. The most represented countries were Indonesia, India and the United Kingdom . Study designs varied considerably: 3 (cluster‐)randomized controlled trials, 2 quasi‐experimental studies, 3 case‐control studies and 3 cohort studies were supplemented by 5 qualitative studies, 2 case studies and a secondary data analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The 19 included studies referred to 15 different intervention programmes. One project pursued 4 different intervention approaches described in 4 publications; results of another programme were described in 2 publications . All interventions aimed at reducing stigmatization for a particular group of patients with a visible chronic skin disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lusli et al [16,17] showed the benefit of psychosocial support like counselling on the leprosy-related stigma. Moreover, Peters et al [18,19] illustrated the success of a contact intervention in Indonesia to reduce leprosy-related stigma in the community. These interventions are likely to work for CL as well.…”
Section: Discussionmentioning
confidence: 99%